Gender-based Livelihood Decisions among Tribal Agricultural Laborers in Wayanad District of Kerala, India - , Shahlas Binth T; , A Anil Kumar (Archives of Current Research International, 2025)
Agricultural workers are among the most overlooked in rural India, facing low income, irregular employment, and harsh working conditions that impact their health. Many belong to scheduled castes and tribes, facing social marginalization and limited opportunities. Their lack of organization further weakens their ability to demand better conditions and rights. In Kerala, the Paniyas are the largest tribal community, mainly residing in Wayanad. Mostly landless or marginal landowners, they depend on agricultural wage labour for survival. Gender inequality is widespread, with women often receiving lower wages and facing unstable work conditions. This study conducts a comprehensive gender analysis of decision-making among tribal agricultural labourers, using a modified procedure developed by Paul (2014). The study analyzed 120 households, selecting 60 male and 60 female tribal agricultural labourers at random. The study found that 68.33% of male respondents lacked control over decisions related to borrowing, such as loan sources, repayment, and amounts. In contrast, 36.67% of women reported full control in these areas. Notably, none of the men had authority over savings or capital transactions, while 63.33% of women independently decided on savings, including the amount and source. Overall, decisions on household management, child care, and finances were mainly made by women, often followed by joint decisions. Men's involvement was limited, largely due to a perceived lack of interest in family matters. The data highlights women's key role in managing household and family affairs, emphasizing the need for gender-sensitive policies that support their contributions. These findings offer valuable guidance for interventions aimed at uplifting tribal agricultural laborers, ensuring gender considerations are effectively addressed in practice.